Osteomielitis supuratif kronis pada mandibula edentulus Chronic suppurative osteomyelitis on edentulous mandible - Leliya Syamsoelily; Surijana Mappangara; M. Hendra Chandha; Muhammad Ruslin (Journal of Dentomaxillofacial Science, 2013)
Osteomyelitis is an infection of the jaw that extends to the jaw bone, which is the spongy, bone marrow, cortex, andperiosteum. Infection occurs in the calcified bone when fluid in the medullary cavity or under the periosteum interferewith the blood supply. In this case, it was reported an elderly patient with a diagnosis of chronic osteomyelitis ofmandible edentulous dextra. The treatment were sequesterectomy and extraction the radix of tooth 43 by generalanesthesia, and combinating with antibiotics. It was concluded that patient of chronic suppurative osteomyelitis of themandible edentulus could be diagnosed through clinical and radiological examination, and successfully treated withsequesterectomy and extracting the radix under general anesthesia. So the improvement of systemic condition, foodnutrition, vitamin therapy, accelerate the healing process. Treatment of focal infection as soon as possible to avoidmore severe complications.